Identification of cytochrome P450 isoenzymes involved in the metabolism of 23-hydroxybetulinic acid in human liver microsomes - Ying Zhou; Jinhua Wen; Guangji Wang (Taylor & Francis Group, 2020)
Context 23-Hydroxybetulinic acid (23-HBA), a major active constituent of Pulsatilla chinensis (Bunge) Regel (Ranunculaceae), exhibits potential antitumor activity. Its metabolism, however, has not yet been studied. Objective This study focuses on the metabolism of 23-HBA in vitro by human liver microsomes. Materials and methods The metabolic kinetics of 23-HBA (0.5-100 µM) and the effects of selective CYP450 (CYP1A2, CYP2C9, CYP2C19, CYP2D6, and CYP3A4) inhibitors on metabolism of 23-HBA were evaluated in human liver microsomes incubation system and then determined by LC-MS method. The Michaelis-Menten parameters Km and Vmax were initially estimated by analysing Lineweaver-Burk plot. The clearance (CLint) was also calculated. Results The Vmax, Km, and CLint of 23-HBA were 256.41 ± 11.20 pmol/min/mg, 11.10 ± 1.07 μM, and 23.10 ± 1.32 μL/min/mg, respectively. The metabolism of 23-HBA was significantly inhibited by furafylline (0.05 μM, p < 0.01) and ketoconazole (0.02 μM, p < 0.05). Ticlopidine (1.3 μM, p < 0.05) could inhibit the metabolism of 23-HBA, while the other inhibitors (sulfaphenazole and quinidine) showed nonsignificant inhibition on the metabolism of 23-HBA. Discussion and conclusions This is the first investigation of the metabolism of 23-HBA in human liver microsomes. The in vitro study indicates that CYP1A2 and CYP3A4 are mainly involved in the metabolism of 23-HBA. Special attention should be given to the pharmacokinetic and clinical outcomes when 23-HBA was co-administrated with other compounds mainly undergoing CYP1A2/CYP3A4-mediated metabolism. Further studies are needed to evaluate the significance of this interaction and strengthen the understanding of traditional Chinese medicine.